Pengelolaan Keuangan Pribadi yang Interaktif Berbasis Android - Giovanni Christian Antonio; Rolly Intan; Rudy Adipranata (Jurnal Infra, 2021)
Technology is currently growing. Many people use smartphones in everyday life, especially Android. In Android, there are many applications that help make everyday life easier for example, applications that help with personal finance. The problem that the author wants to solve is personal finance applications between applications with different features and completeness for recording. In solving this problem, the author adds features from existing personal finance applications such as speech to text for input, recurring transactions, and calculating installments whether you can pay in installments or not. Based on the results of the tests that have been carried out, the application made is successful in recording finances and adding good features such as speech to text, recurring transactions, and calculating installments by looking at income and expenses. The results of the questionnaire show an average of 4.54 for interactive personal financial management applications.